2021
DOI: 10.1155/2021/8886557
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Response Analyses of Plastic Greenhouse Structure considering Fluctuating Wind Load

Abstract: Wind load is one of the main factors of plastic greenhouse collapse. To solve the dynamic response problem of greenhouses under wind load and determine the dangerous section of a skeleton structure, the investigated lump method is presented for the dynamic response analysis of a plastic greenhouse, considering pulsating wind on the basis of Timoshenko beam theory. First, the investigated lump is designed according to the Timoshenko beam microbody concept. On the basis of Timoshenko beam theory, the governing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The value of gravitational acceleration is closely related to latitude and altitude. The gravitational acceleration at an altitude of 0 m at a certain latitude can be obtained from Equation (3). Then, the resulting value can be corrected for altitude using Equation ( 4) to obtain the value of gravity, taking latitude and altitude into account [32].…”
Section: Gravitational Accelerationmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of gravitational acceleration is closely related to latitude and altitude. The gravitational acceleration at an altitude of 0 m at a certain latitude can be obtained from Equation (3). Then, the resulting value can be corrected for altitude using Equation ( 4) to obtain the value of gravity, taking latitude and altitude into account [32].…”
Section: Gravitational Accelerationmentioning
confidence: 99%
“…The solar greenhouse framework is distinguished by its lightweight construction; expansive span; and elongated, slender poles, collectively constituting a flexible structural paradigm. Furthermore, the roofing materials employed in solar greenhouses are characterized by their lightweight nature and susceptibility to wind dynamics [2,3]. Incidents of high winds causing damage to solar greenhouse roofs and their supporting structures have intermittently occurred, leading to substantial economic losses and disruptions in normal production.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a PVC mini greenhouse can be easily folded [12][13]. On the other hand, the impact of wind load on the mini greenhouse should not reduce its stability [14][15]. So, the stiffeners are added.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Using a large-sized wind tunnel, the wind pressure distribution and local damage of a large-span circular arch greenhouse built in coastal areas were studied 9 . It is suggested that the damage caused by the bending moment due to a strong wind load should be considered in the calculation of the wind pressure coefficient in structural design 10 . Briassoulis et al 11 established a three-dimensional structure model and a two-position frame model of a large multi-span circular arch greenhouse.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic response mechanism of greenhouse structures under dynamic loads needs further theoretical research. In our previous work, a block method was proposed for the dynamic response analysis of a solar greenhouse with a plane rigid frame model under wind load 13 . The wind-induced vibration responses of a 12 m span truss solar greenhouse were also investigated by the time domain method 14 .…”
Section: Introductionmentioning
confidence: 99%